2002
DOI: 10.1046/j.1525-139x.2002.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis in Anuric Patients: Concerns and Cautions

Abstract: Most recent studies have found an equivalent survival for patients on peritoneal dialysis (PD) and hemodialysis (HD); evidence even suggests that PD might be the preferred modality during the first 3-4 years of renal replacement therapy. This is probably related to the continuous and minimally invasive character of PD as compared to HD, resulting in better preservation of residual renal function (RRF) and less cardiovascular strain. On the other hand, blood pressure control, fluid balance, and adequacy targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The CANUSA study (43) emphasized the importance of RRF for patients on PD, and a reanalysis of the data using a survival model, which took into account the time‐dependent decline in RRF, demonstrated that RRF was a key factor in survival, rather than dialysis solute clearance (44). The benefits of RRF in PD extend beyond survival and there is good evidence that it has a beneficial effect on anemia (45,46), blood pressure (47), hypervolemia (48), left ventricular hypertrophy (45), nutrition (49,50), and bone metabolism (51).…”
Section: Outcome Benefits Of Preserved Rrf In Pdmentioning
confidence: 99%
“…The CANUSA study (43) emphasized the importance of RRF for patients on PD, and a reanalysis of the data using a survival model, which took into account the time‐dependent decline in RRF, demonstrated that RRF was a key factor in survival, rather than dialysis solute clearance (44). The benefits of RRF in PD extend beyond survival and there is good evidence that it has a beneficial effect on anemia (45,46), blood pressure (47), hypervolemia (48), left ventricular hypertrophy (45), nutrition (49,50), and bone metabolism (51).…”
Section: Outcome Benefits Of Preserved Rrf In Pdmentioning
confidence: 99%
“…9,10 And beyond survival benefits, RRF has been shown to have beneficial effects on anaemia, blood pressure control, hypervolaemia, left ventricular hypertrophy, bone metabolism and nutrition. [11][12][13][14][15][16] There are many similarities between factors affecting the rate of decline in RRF in dialysis and those affecting the rate of GFR decline in CKD. However, to our knowledge, there is little information on the clinical impact of serum UA levels on the RRF of PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The current guidelines are therefore speculative for anuric patients on PD. Indeed, anuric patients are a difficult group to dialyze effectively using CAPD (7). Not only may membrane permeability increase with time on PD with a consequent decrease in achieved UF (8), but also it is difficult to increase dialysis small solute clearance using CAPD because of the practical difficulties in increasing exchange volume and/or number.…”
mentioning
confidence: 99%